Far-Field Tsunami Impact in the North Atlantic Basin from Large Scale Flank Collapses of the Cumbre Vieja Volcano, La Palma - Tehranirad, Babak; Harris, Jeffrey C.; Grilli, Annette R.; Grilli, Stephan T.; Abadie, Stéphane; Kirby, James T.; Shi, Fengyan (Pure and Applied Geophysics, 2015)
In their pioneering work, Ward and Day suggested that a large scale flank collapse of the Cumbre Vieja Volcano (CVV) on La Palma (Canary Islands) could trigger a mega-tsunami throughout the North Atlantic Ocean basin, causing major coastal impact in the far-field. While more recent studies indicate that near-field waves from such a collapse would be more moderate than originally predicted by Ward and Day [Løvholt et al. (J Geophy Res 113:C09026, 2008); Abadie et al. (J Geophy Res 117:C05030, 2012)], these would still be formidable and devastate the Canary Island, while causing major impact in the far-field at many locations along the western European, African, and the US east coasts. Abadie et al. (J Geophy Res 117:C05030, 2012) simulated tsunami generation and near-field tsunami impact from a few CVV subaerial slide scenarios, with volumes ranging from 20 to 450 km3; the latter representing the most extreme scenario proposed by Ward and Day. They modeled tsunami generation, i.e., the tsunami source, using THETIS, a 3D Navier-Stokes (NS) multi-fluid VOF model, in which slide material was considered as a nearly inviscid heavy fluid. Near-field tsunami impact was then simulated for each source using FUNWAVE-TVD, a dispersive and fully nonlinear long wave Boussinesq model [Shi et al. (Ocean Modell 43–44:36–51, 2012); Kirby et al. (Ocean Modeling, 62:39–55, 2013)]. Here, using FUNWAVE-TVD for a series of nested grids of increasingly fine resolution, we model and analyze far-field tsunami impact from two of Abadie et al.’s extreme CVV flank collapse scenarios: (i) that deemed the most “credible worst case scenario” based on a slope stability analysis, with a 80 km3 volume; and (ii) the most extreme scenario, similar to Ward and Day’s, with a 450 km3 volume. Simulations are performed using a one-way coupling scheme in between two given levels of nested grids. Based on the simulation results, the overall tsunami impact is first assessed in terms of maximum surface elevation computed along the western European and ...